Low temperature selective oxidation of methane to methanol using titania supported gold palladium copper catalysts - Mohd Hasbi, Ab. Rahim; Robert, D. Armstrong; Ceri, Hammond; Nikolaos, Dimitratos; Simon, J. Freakley; Michael, M. Forde; David, J. Morgan; Georgi, Lalev; Robert, L. Jenkins; Jose Antonio, Lopez-Sanchez; Stuart, H. Taylor; Graham, J. Hutchings (Royal Society of Chemistry, 2016)
The selective oxidation of methane to methanol has been studied using trimetallic AuPdCu/TiO2 catalysts prepared by incipient wetness impregnation. They are able to catalyse the selective oxidation of methane to methanol under mild aqueous reaction conditions using H2O2 as the oxidant. When compared with bimetallic,Au–Pd/TiO2 analogues, the new trimetallic catalysts present productivities which are up to 5 times greater under the same test conditions, and this is coupled with methanol selectivity of up to 83%. Characterisation shows that whilst Au–Pd is present as Au-core–Pd-shell anoparticles, copper is present as either Cu or Cu2O in <5 nm particles